Annona atemoya leaf extract ameliorates cognitive impairment in amyloid-β injected Alzheimer's disease-like mouse model. Issue 18 (December 2019) - Lim, Hye-Sun; Kim, Yu Jin; Sohn, Eunjin; Yoon, Jiyeon; Kim, Bu-Yeo; Jeong, Soo-Jin
Annona atemoya is a hybrid of Annona squamosa and Annona cherimola that grow in several subtropical or tropical areas such as Florida in the US, Philippines, Cuba, Jamaica, Taiwan, and Jeju in South Korea. We report that the A. atemoya leaves (AAL) have inhibitory effects on the pathogenesis and regulatory mechanisms of Alzheimer's disease (AD). Ethanol extract of AAL prevented amyloid-β (Aβ) aggregation and increased free radical scavenging activity. In addition, AAL extract exerted protective effects against neuronal cell death in HT22 hippocampal cells. Moreover, oral administration of AAL extract significantly improved memory loss in the passive avoidance task and Y-maze test, as well as downregulated the expression of neuronal markers neuronal nuclei and brain-derived neurotrophic factor in Aβ-injected AD mice. To verify the molecular mechanisms responsible for anti-AD actions of AAL, we conducted the antibody microarray analysis and found that epidermal growth factor receptor/G protein-coupled receptor kinase 2 signaling was activated in neuronal cells and AD-like mouse models. Additionally, quantitative analyses of the six standard compounds using high-performance liquid chromatography revealed that rutin is the most abundant compound of AAL. Furthermore, efficacy analyses of six standard compounds showed that rutin and isoquercitrin had significant inhibitory activity on Aβ aggregation. Taken together with biological activity and the content of compounds, rutin maybe a bioactive compound of AAL in the AD pathogenesis. Overall, our findings provide the first scientific support for the therapeutic effects of AAL in AD and AD-related disorders. Impact statement: Our study was aimed to find a novel candidate drug for Alzheimer's disease (AD) using natural products. We assessed the effects of Annona atemoya extracts on crucial events in the pathogenesis of AD. A. atemoya leaf (AAL) extract significantly inhibited amyloid-β aggregation, oxidative stress, neuronal cell death, and memory impairment through the epidermal growth factor receptor/G protein-coupled receptor kinase 2 pathway. Simultaneous analysis using HPLC determined six standard compounds of AAL extract, and rutin was identified as a bioactive compound. Of note, the anti-AD activity of AAL extract was more significant compared to other extracts from medicinal plants of which efficacy was previously reported. The potential of AAL extract as an anti-AD agent may provide insight into the new drug development for AD treatment.